Relative functionality attributes of right and left ovaries in buffaloes (Buhalus bubalis) - GUPTA, P S P; NANDI, S; SARMA, P V (The Indian Journal of Animal Sciences, 2014)
Proper implementation of reproductive technologies in buffalo, a species of high dairy merits, necessitates in depth studies on its ovarian functions. Present study aimed to elucidate the relative functionality attributes of right. and left buffalo ovaries of slaughtered mature riverine buffaloes. Weight of the ovary (2.53 and 2.65 g), follicular fluid volume per ovary (0.19 and 0.24). the number of follicles (4.97 and 5.12), oocytes (3.14 and 3.23), corpora lutea (0.37 and 0.41) and corpora albicans (0.31 and 0.20) present in the right and their left ovaries. respectively, were not significantly different. These results suggest equal participation of the right and the left ovary in reproductive functions of buffalo.